2003
DOI: 10.1016/s0006-8993(03)02354-0
|View full text |Cite
|
Sign up to set email alerts
|

Survey of 21 inbred mouse strains in two laboratories reveals that BTBR T/+ tf/tf has severely reduced hippocampal commissure and absent corpus callosum

Abstract: A morphometric survey of brain size and forebrain commissures of 21 inbred mouse strains from the Jackson Laboratory was done with animals tested in two laboratories as part of the Mouse Phenome Project. Strain BTBR T / + tf/tf was found to have 100% total absence of the corpus callosum as well as severe reduction of the hippocampal commissure in almost every animal, the most severe commissure defect observed to date in any commercially available mouse strain. The strain 129S1/SvImJ had a milder defect with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
154
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(175 citation statements)
references
References 24 publications
20
154
1
Order By: Relevance
“…DTI is a technique that examines the underlying tissue microstructure based on the diffusion of water throughout the brain. The most striking difference between BTBR and both of the control strains was the almost complete lack of a corpus callosum, as previously reported [150]. Cerebral white matter as a whole was significantly reduced, specifically 10 of 14 with matter regions were smaller.…”
Section: Recent Investigations (2010-14)supporting
confidence: 77%
“…DTI is a technique that examines the underlying tissue microstructure based on the diffusion of water throughout the brain. The most striking difference between BTBR and both of the control strains was the almost complete lack of a corpus callosum, as previously reported [150]. Cerebral white matter as a whole was significantly reduced, specifically 10 of 14 with matter regions were smaller.…”
Section: Recent Investigations (2010-14)supporting
confidence: 77%
“…ANOVAs comparing all possible pairs of data sets and details of methods for measuring brains in each study are provided in Tables 1 and 2 and Supporting Text, which are published as supporting information on the PNAS web site. The Edmonton and Portland strain means were very similar indeed (r ϭ 0.98), and average weights across all strains were almost identical at the two sites (0.452 and 0.456 g, respectively) (15). Methods of fixation were very similar in the Williams (16) study, and the correlation of Edmonton data with their strain means was very high (r ϭ 0.88).…”
mentioning
confidence: 73%
“…BTBR mice do not demonstrate significant quadrant selectivity after reversal learning in the Morris water maze task, which may indicate a resistance to change in this strain [49]. It is possible that the behavioral phenotype of low social approach [8,49] and failure to modify behavioral patterns in the hole-board familiarization assay might be related to the overt neuroanatomical defects in these mice, including absent corpus callosum and reductions in the hippocampal commissure [82]. Some studies have reported deficiencies in corpus callosum volume or white matter concentration in autistic patients [1,13,41,61,81,83].…”
Section: Discussionmentioning
confidence: 99%
“…82 Figure 12 depicts the results from the olfactory stimuli tests, before and after familiarization, in the wildtype and NMDA receptor-deficient mice. Before familiarization, the wildtype mice evidenced an extreme preference for the familiar cage bedding, with almost 40% of the total responses across the 16 holes directed toward this olfactory stimulus.…”
Section: Studymentioning
confidence: 99%